Expanding Interaction Potentials within Virtual Environments: Investigating the Usability of Speech and Manual Input Modes for Decoupled Interaction. (28th November 2011) - Stedmon, Alex; Bayon, Victor; Griffiths, Gareth
Abstract : Distributed technologies and ubiquitous computing now support users who may be detached or decoupled from traditional interactions. In order to investigate the potential usability of speech and manual input devices, an evaluation of speech input across different user groups and a usability assessment of independent-user and collaborative-user interactions was conducted. Whilst the primary focus was on a formative usability evaluation, the user group evaluation provided a formal basis to underpin the academic rigor of the exercise. The results illustrate that using a speech interface is important in understanding user acceptance of such technologies. From the usability assessment it was possible to translate interactions and make them compatible with innovative input devices. This approach to interaction is still at an early stage of development, and the potential or validity of this interfacing concept is still under evaluation; however, as a concept demonstrator, the results of these initial evaluations demonstrate the potential usability issues of both input devices as well as highlighting their suitability for advanced virtual applications.